Effects of heat, elevated vapor pressure deficits and growing season length on growth trends of European beech - Leuschner, Christoph; Bat-Enerel, Banzragch (Frontiers in Forests and Global Change, 2024)
In recent decades, continued growth decline has been observed in various beech forest regions of Central and Western Europe, especially in the warmer lowlands, which is not necessarily linked to increased mortality. While earlier dendrochronological studies have shown that a deteriorating climatic water balance in the course of climate warming can drive negative growth trends, less is known about the effects of climatic extremes on tree growth, notably heat and rising atmospheric vapor pressure deficits (VPD). Through climate-growth analysis, we analyzed the influence of summer heat duration (frequency of hot days with Tmax > 30°C) and elevated VPD on the basal area increment (BAI) of dominant beech trees in 30 stands across a precipitation gradient in the northern German lowlands. Summer heat (especially in June) and elevated VPD are reducing BAI in a similar manner as does a deteriorated climatic water balance. While growing season length (GSL), derived from thermal thresholds of growth activity, has substantially increased since 1980, BAI has declined in the majority of stands, demonstrating a recent decoupling of tree productivity from GSL. We conclude that heat and elevated VPD most likely are important drivers of the recent beech growth decline in this region, while growing season length has lost its indicative value of beech productivity.